Multicomponent Tandem Triple Functionalization of Indoles via a Directing‐group‐free Strategy. Issue 7 (24th March 2023) - Gu, Xiaoting; Zhang, Xiaoxiang; Yu, Wenhua; Sun, Ke; Wei, Wanxing; Zhang, Zhuan; Liang, Taoyuan
Abstract: The position‐selective functionalization of the poorly reactive benzenoid nucleus of indoles has remained a great challenge in organic chemistry. Here we describe a directing‐group‐free, three‐component tandem C3‐acylation/C5, 6‐H disulfenylation of indoles via an iodine‐, Lewis acid‐ and Brønsted acid‐cooperated mediated strategy. This protocol is remarkable for its exceptional regio‐ and chemo‐selectivity, broad substrate scope, good functional group tolerance and mild reaction conditions. Advantageously, the present protocol offers great potential for the development of general site‐selective functionalization at the benzenoid nucleus of indoles, removing the requirement for neighbouring activating groups. Abstract :